BANGUNAN MASJID PADA MASA NABI DAN IMPLIKASINYA TERHADAP JAMAAH MASJID PEREMPUAN - Syafi, M. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
In this article, the writer focuses on a mosque built in the time of Mohammad,Â and analyses the implications of its construction towards the way that women worship in it. Some of its implications are shown in such sayings and hadiths that seem decidedly misogynic, such as â€œThe worst place in prayer for women at the forefrontâ€ or â€œA woman can break the legitimacy of a prayerâ€, as well as â€œThe best place for a women to pray is at homeâ€ or that â€œWomen should only go to the mosque with their husbandsâ€. The understanding of such hadiths is explored by the writer contextually to reduce or allay gender bias in the interaction between men and women in the mosque. Based on contextual analysis, it is found that cultural, geographical, and structural and even the condition of local facilities are all deciding factors that influence the design and layout of mosques, which in turn influences the position and interaction between the mosque as a place and women as its users. With this in mind, a call to rethink the meaning of such discriminative hadiths is certainly in order.